2020
DOI: 10.37080/nmj.41
|View full text |Cite
|
Sign up to set email alerts
|

Caudal Epidural for Pain Management of Prostate Cancer

Abstract: Introduction:Methods: Results:Conclusions:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Current study shows that male children were predominantly admitted compared to females. Similar findings were found in the study conducted by Joshi, et al 12 and others. 13 , 14 This could be due to higher acceptance of parents to admit their sons compared to their daughters 15 but could also be due to the variable gender composition of the study population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Current study shows that male children were predominantly admitted compared to females. Similar findings were found in the study conducted by Joshi, et al 12 and others. 13 , 14 This could be due to higher acceptance of parents to admit their sons compared to their daughters 15 but could also be due to the variable gender composition of the study population.…”
Section: Discussionsupporting
confidence: 92%
“…Such findings were similar to the study done in Kanti Children Hospital (KCH). 12 Current study shows that male children were predominantly admitted compared to females. Similar findings were found in the study conducted by Joshi, et al 12 and others.…”
Section: Discussionmentioning
confidence: 82%
“…The intermittent supply of water in urban areas like Kathmandu and Bharatpur causes crosscontamination of water distribution channels and sewage systems posing a threat to public health (Cairncross & Feachem 2019). Joshi et al (2019) reported enteric fever cases throughout the year with 43.06% of cases in the rainy and summer season between May to August. In this study, on a monthly basis, we observed that most cases (20.2%) were in June and the least was in both January and October with 1.9% of cases in each.…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal occurrence of enteric fever is found to be variable in various regions throughout the globe (Saad et al 2018). In Nepal, enteric fever is predominant mostly in the rainy season (Singh et al 2011, Joshi et al 2019. Implementation of strategies of addressing environmental factors like improved public sanitation and provision of safe drinking water at the local level aids to decrease the risk of acquired enteric fever (Bhutta et al 2018).…”
Section: Introductionmentioning
confidence: 99%